Fiscal policy, inequality, and the poor in the developing world - Nora Lustig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Using comparable fiscal incidence analysis, this paper examines the impact of fiscal policy on inequality and poverty in 25 countries for around 2010. Success in fiscal redistribution is driven primarily by redistributive effort (share of social spending to GDP in each country) and the extent to which transfers/subsidies are targeted at the poor and direct taxes targeted at the rich. While fiscal policy always reduces inequality, this is not the case with poverty. Fiscal policy increases poverty in 4 countries using a US1.25/day PPP poverty line, in 8 countries using a US2.50/day line, and in 15 countries using a US4/day line (over and above market income poverty). Net direct taxes are always equalizing and net indirect taxes are equalizing in 17 of the 25 countries. While spending on pre-school and primary school is pro-poor (i.e. the per capita transfer declines with income) in almost all countries, pro-poor secondary school spending is less prevalent, and tertiary education spending tends to be progressive only in relative terms (i.e. equalizing but not pro-poor). Health spending is always equalizing.
Keywords: H22; H5; H50; D31; I3; I30; 330; fiscal incidence; social spending; inequality; poverty; developing countries